2021
DOI: 10.1111/cen.14445
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenesis in patients with adrenal incidentalomas: Extended steroid profile measured by liquid chromatography‐mass spectrometry after ACTH stimulation and dexamethasone suppression

Abstract: Objective Describe the secretion and profile of adrenal steroids in patients with adrenal incidentalomas compared to control subjects. Design, Setting and Participants A prospective study, 73 patients with adrenal incidentalomas, 21 bilateral and 52 unilateral and 34 matched controls in University Hospital. Methods Collect fasting blood sample before and 60 min after ACTH test (250 µg IV). One week later, perform overnight 1 mg dexamethasone test. The following steroids were measured by liquid chromatography‐m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The first original result of this study is that the seven steroids studied, distributed on the three adrenal steroidogenesis pathways (glucocorticoids, androgens and mineralocorticoids), presented a higher amplitude of response to ACTH in patients with bilateral tumors (BL) not only in comparison to control subjects (CT) but also in comparison to patients with UL tumors. The only previous study comparing steroid profiles after ACTH stimulation between control subjects, UL and BL adrenocortical tumors ( 23 ) only looked at basal (T0) and stimulated (T60) steroid levels in absolute value and did not describe steroid amplitude of response to ACTH. Besides, patients’ recruitment was rather different: bilateral tumors only consisted in bilateral incidentalomas (no case of PBMAH reported).…”
Section: Discussionmentioning
confidence: 99%
“…The first original result of this study is that the seven steroids studied, distributed on the three adrenal steroidogenesis pathways (glucocorticoids, androgens and mineralocorticoids), presented a higher amplitude of response to ACTH in patients with bilateral tumors (BL) not only in comparison to control subjects (CT) but also in comparison to patients with UL tumors. The only previous study comparing steroid profiles after ACTH stimulation between control subjects, UL and BL adrenocortical tumors ( 23 ) only looked at basal (T0) and stimulated (T60) steroid levels in absolute value and did not describe steroid amplitude of response to ACTH. Besides, patients’ recruitment was rather different: bilateral tumors only consisted in bilateral incidentalomas (no case of PBMAH reported).…”
Section: Discussionmentioning
confidence: 99%
“…Eisenhofer et al 27 observed that additional preanalytical factors, such as age, weight and blood pressure may modify the ACTH response of this unique steroid, but we and others 17 have not checked for that. Moreover, increased 21DF levels are observed beyond CAH context, for example, subclinical cortisol adenomas, primary aldosteronism, adrenal incidentalomas and cholangiocarcinoma 28–32 ; conversely, 21OHD HZ status has not also been investigated in these conditions 33 …”
Section: Discussionmentioning
confidence: 99%
“…Their synthesis is controlled by the Hypothalamic Pituitary Adrenal axis and the Hypothalamic Pituitary Gonadal axis and they have roles in many physiological and pathophysiological processes. Measuring panels of steroids is important clinically in assessing endocrine function, reproductive health and in cancer [2] , [3] , [4] and also in veterinary care and welfare in animals [5] , [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%